Euthanasia, assisted suicide and palliative care: analysis of the document of the EAPC Ethics Task Force. - Spagnolo, Antonio G.; Comoretto, Nunziata (Medicina e Morale, 2004)
In June 2003 EAPC adopted a document on the ethics of euthanasia and physician-assisted suicide as official position of the association. With this document EAPC actively intended to insert itself in the wide debate that involves the end-of-life issues and the care of the terminally ill patient, according with the peculiar perspective of palliative care. The first positive issue offered by the document concerns the methodological aspect: the document offers an explanation of broadly employees concepts and definitions, frequently cause of misunderstandings: it emerges especially uselessness and ambiguity of the distinction, until too misused, between "active" and "passive" euthanasia. Some points of the document seem particularly meaningful: the role of the palliative care in strengthening the autonomy of the patient and in opposing euthanasia and physician-assisted suicide request; the different meaning of euthanasia in comparison to the so-called "terminal sedation". Authors notice in the document some problematic knots, close to the positive aspects: an ambiguous reference to the employment of anticipated directives and, above all, the explicit abstention from something about the norms and values associated with euthanasia and physician-assisted suicide, when instead ample reference to norms and values is made about palliative care. Affirmed neutrality in front of individual choices in favour of these behaviours cannot be accepted from a document on the ethics, which would have owed to push to say something more on what "should be".